Instytucja pożyczkodawcy ostatniej instancji - na przykładzie Międzynarodowego Funduszu Walutowego - Frankiewicz, Damian (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
A global lender of last resort is an institution that plays a significant role in an international financial system. It was clearly brought into the limelight by the recent financial crisis. The existence of this institution is strongly justified by the volume and volatility of global capital flows, the increasing financial and economic interlinkages between the countries, as well as the consequent possibility of the spill over effects. The article argues that the International Monetary Fund appears to be the only international financial institution capable of acting as a global lender of last resort and thus ensuring stability of the international financial system. The IMF has proven useful in providing liquidity support to countries struggling with financial dificulties in recent years. It is equipped with adequate financial resources, lending facilities tailored to address the specific circumstances of its members, highly qualified staff and the coordination capacities at the international level, which are indispensable to forestall the crisis in the global economy